Benthic solute exchange and carbon mineralization in two shallow subtidal sandy sediments: Effect of advective pore‐water exchange - Perran L. M. Cook; Frank Wenzhöfer; Ronnie N. Glud; Felix Janssen; Markus Huettel (Limnology and Oceanography, 2007)
We conducted four field campaigns to evaluate benthic O 2 consumption and the effect of advective pore‐water flow in nearshore permeable sediments in the North Sea and Baltic Sea. Advective pore‐water transport had a marked effect on the benthic exchange of O 2 and TCO 2 in benthic chamber incubations, with the rates of exchange increasing by a factor of up to 2.5 when imposing flushing rates of 100‐300 L m −2 d −1 , compared to settings with diffusive exchange only. Estimates of in situ exchange rates using oxygen penetration and volumetric O 2 consumption and TCO 2 production rates were within the range measured in the chambers. The contribution of advection to solute exchange was highly variable and dependent on sediment topography. Advective processes also had a pronounced influence on the in situ distribution of O 2 within the sediment, with characteristic two‐dimensional patterns of O 2 distribution across ripples, and also deep subsurface O 2 pools, being observed. Mineralization pathways were predominantly aerobic when benthic mineralization rates were low and advective pore‐water flow high as a result of well‐developed sediment topography. By contrast, mineralization proceeded predominantly through sulfate reduction when benthic mineralization rates were high and advective pore‐water flow low as a result of poorly developed topography. Previous studies of benthic mineralization in shallow sandy sediments have generally ignored these dynamics and, hence, have overlooked crucial aspects of permeable sediment function in coastal ecosystems.